River temperature analysis with a new way of using Independant Component Analysis - Moulin, Nelly; Gresselin, Frederic; Dardaillon, Bruno; Thomas, Zahra (Frontiers in Earth Science, 2022)
In the context of global warming, river management is essential to maintain favourable water temperature ranges for aquatic species. Therefore, understanding the main factors influencing the water temperature becomes a key part in the management process. In this paper, we used Independent Component Analysis (ICA) to identify these main factors and improve water temperature forecasting. The study is carired out on 2 rivers in Normandy (France) with quite different characteristics. Each river was equipped with several temperature sensors which series range from 2011 to 2021. The ICA analysis of the data series reveals that the thermal regime of these two rivers is mainly controlled by seasonal and daily climatic factors. The Sélune regime also turns out to be influenced by the presence of a dam, dismantled during the monitoring of the river. The temperature of the Odon appears to be clearly controlled by seasonal lightening conditions in connection with the presence of the riparian vegetation. Complementary, an innovative approach called "successive ICA" is used to reconstruct the natural thermal regime of the Sélune